2013
DOI: 10.3109/15376516.2012.762082
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for assessing the role of iron and its functional chelation in fibrin fibril formation: the use of scanning electron microscopy

Abstract: Scanning electron microscopy shows that iron-chelating agents are effective inhibitors of DMD formation. The most active inhibitors of DMD formation proved to be Desferal, Clioquinol and Curcumin, whereas Epigallocatechin gallate and Deferiprone were less effective. The functional model we describe may point the clinical utility of various substances in iron-mediated degenerative diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 70 publications
4
60
0
Order By: Relevance
“…HO-1 activity is also increased systemically in inflammatory disorders associated with thrombophilia, such as diabetes mellitus [21] and rheumatoid arthritis [22]. Critically, SEM-based investigations demonstrated that the fibrin matrix formed from blood obtained from individuals with diabetes mellitus [23] or rheumatoid arthritis [24] was very similar to that observed when normal blood was exposed to ferric chloride [2][3][4][5][6][7]. In a complementary fashion, using a viscoelastic methodology validated to detect carbon monoxide-mediated hypercoagulability in the setting of tobacco smoking [25], it was determined that a patient with a clotted ventricular assist device and hemolysis had carbon monoxide-mediated hypercoagulability, and upregulation of HO-1 was documented by increased carboxyhemoglobin concentrations [26].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…HO-1 activity is also increased systemically in inflammatory disorders associated with thrombophilia, such as diabetes mellitus [21] and rheumatoid arthritis [22]. Critically, SEM-based investigations demonstrated that the fibrin matrix formed from blood obtained from individuals with diabetes mellitus [23] or rheumatoid arthritis [24] was very similar to that observed when normal blood was exposed to ferric chloride [2][3][4][5][6][7]. In a complementary fashion, using a viscoelastic methodology validated to detect carbon monoxide-mediated hypercoagulability in the setting of tobacco smoking [25], it was determined that a patient with a clotted ventricular assist device and hemolysis had carbon monoxide-mediated hypercoagulability, and upregulation of HO-1 was documented by increased carboxyhemoglobin concentrations [26].…”
Section: Introductionmentioning
confidence: 95%
“…First, it was posited, and then determined that iron modified fibrinogen, which enhanced coagulation and attenuated fibrinolysis as documented by spectrophotometric and scanning electron micrographic (SEM) techniques [1][2][3][4][5][6][7]. Second, it was serendipitously discovered that carbon monoxide enhanced fibrinogen-dependent coagulation via an associated heme(s) group and attenuated fibrinolysis via upregulation of a 2 -antiplasim activity and downregulation of plasmin activity via enzyme-associated heme(s) [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…389,406 It has also been suggested that added ferric iron can carry out Fenton chemistry by reacting with peroxide that may be formed in a variety of ways. 171,353,359,407,408 Thus both electrostatic phenomena and hydroxyl radical formation may modify the fibrinogen structure in such a way that its kinetics of polymerisation, and the structure of the fibrin products, is altered substantially. 3 and YCl 3 (final concentration 15 mM) were mixed with platelet rich plasma (PRP) from 6 healthy individuals prepared from blood drawn in citrate tubes.…”
Section: Electrostatic Considerationsmentioning
confidence: 99%
“…Fibrin fibres were prepared for SEM according to methods published previously. 359,360 SEM analysis of healthy fibrin fibre morphology (Fig. 8A) shows individual fibres that form a typical netlike structure.…”
mentioning
confidence: 99%
“…The coagulation cascade is the vital component that maintains the balance required for hemostasis by activating platelets and forming a hemostatic platelet plug as well as stabilizing fibrin networks, contributing to blood clot formation [27,28]. Laboratory-based investigations of fibrin structures, platelet morphology, and the fibrin clot in general has become a popular and powerful research tool as these structural findings could differ in and provide essential information on various diseased states possibly contributing to the discovery of new therapeutic targets [29,30].…”
Section: Discussionmentioning
confidence: 99%